Pencapaian Skill Menulis Bahasa Arab dengan Media Gambar - Nor Holis Bin Nafsah; Angga Hidayat (INAIFAS Press, 2022)
An appropriate media and suitable to students' conditions are essential in the Arabic language learning process, especially for Arabic learning in an Islamic school. Through this research, we wanted to check student learning achievement in the aspect of mahārah al-kitābah through picture media that we applied to 10th-grade students at Madrasah Aliyah Assunniyyah Kencong Jember. The method used in this research was the qualitative method. Through picture media, the average student score was 70.5 based on the indicators we set, and they were pretty capable of Arabic writing skills. Therefore, the picture media we use can make students master mahārah al-kitābah.